Hyperspectral Measurements, Parameterizations, and Atmospheric Correction of Whitecaps and Foam From Visible to Shortwave Infrared for Ocean Color Remote Sensing - Dierssen, Heidi M. (Frontiers in Earth Science, 2019)
Breaking waves are highly reflective features on the sea surface that change the spectral properties of the ocean surface in both magnitude and spectral shape. Here, hyperspectral reflectance measurements of whitecaps from 400-2500 nm were taken in Long Island Sound, USA of natural and manufactured breaking waves to explore new methods to estimate whitecap contributions to ocean color imagery. Whitecap reflectance was on average ~40% in visible wavelengths and decreased significantly into the near infrared and shortwave infrared following published trends. The spectral shape was well-characterized by a third order polynomial function of liquid water absorption that can be incorporated into coupled ocean-atmospheric models and spectral optimization routines. Localized troughs in whitecap reflectance correspond to peaks in liquid water absorption and depths of the troughs are correlated to the amount and intensity of the breaking waves. Specifically, baseline-corrected band depths at 980 and 1200 nm explained 77% and 90% of the whitecap-enhanced reflectance on a logarithmic scale, respectively. Including these wavebands into future ocean color sensors could potentially provide new tools to estimate whitecap contributions to reflectance more accurately than with wind speed. An effective whitecap factor was defined as the optical enhancements within a pixel due to whitecaps and foam independent of spatial scale. A simple mixed-pixel model of whitecap and background reflectance explained as much of the variability in measured reflectance as more complex models incorporating semi-transparent layers of foam. Using an example atmosphere, enhanced radiance from whitecaps was detectable at the top of the atmosphere and a multiple regression of at-sensor radiance at 880, 1038, 1250 and 1615 nm explained 99% of the variability in whitecap factor. A proposed model of whitecap-free reflectance includes contributions from water-leaving radiance, glint, and diffuse reflected skylight. The epsilon ratio at 753 and 869 nm commonly used for aerosol model selection is nearly invariant with whitecap factor compared to the ratio at shortwave infrared bands. While more validation data is needed, this research suggests several promising avenues to retrieve estimates of the whitecap reflectance and to use ocean color to further elucidate the physics of wave breaking and gas exchange.